2020
DOI: 10.3390/rs12071139
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Plant Nitrogen Concentration of Maize Using a Leaf Fluorescence Sensor across Growth Stages

Abstract: Nitrogen (N) is one of the most essential nutrients that can significantly affect crop grain yield and quality. The implementation of proximal and remote sensing technologies in precision agriculture has provided new opportunities for non-destructive and real-time diagnosis of crop N status and precision N management. Notably, leaf fluorescence sensors have shown high potential in the accurate estimation of plant N status. However, most studies using leaf fluorescence sensors have mainly focused on the estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 81 publications
1
8
0
Order By: Relevance
“…Simulated by a crop model (CERES-Maize) based on field experiments and historical weather information, the long-term economic optimal N rate in this study site was found to be 198 ± 35 kg ha −1 [51]. However, after reaching the optimal N level, little excessive N was accumulated by luxury N uptake, and the N concentration in maize plants did not change significantly [35]. This led to the indistinctive variation of the fluorescence indices under the two high N rates.…”
Section: Detection Of N Variability In Maize Using Fluorescence Param...mentioning
confidence: 84%
See 1 more Smart Citation
“…Simulated by a crop model (CERES-Maize) based on field experiments and historical weather information, the long-term economic optimal N rate in this study site was found to be 198 ± 35 kg ha −1 [51]. However, after reaching the optimal N level, little excessive N was accumulated by luxury N uptake, and the N concentration in maize plants did not change significantly [35]. This led to the indistinctive variation of the fluorescence indices under the two high N rates.…”
Section: Detection Of N Variability In Maize Using Fluorescence Param...mentioning
confidence: 84%
“…Among them, the application of the normalized N sufficient index (NSI) is a very common procedure that has been used in many studies [18,32,34]. A recent study proposed a modified approach to estimate maize PNC across growth stages based on the use of days after sowing (DAS) [35].…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of chlorophyll to flavonoids is the nitrogen balance index, which is an important indicator of the nitrogen status in plants and reflects the growth of plants and the degree of absorption and utilization of proteins by the organism (Dong et al, 2020). DS can inhibit the absorption of nitrogen by plants, resulting in insufficient nutrient supply in plants (Sarhadi et al, 2020), while AMF can improve the absorption of nitrogen and maintain normal nutrient supply (He et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Leaf and plant N concentrations (LNC, PNC) have been used as vital parameters of crop N status [ 5 ]. However, N concentrations are dependent on the plant biomass, such that two different plants with the same N concentration but differ in plant biomass.…”
Section: Introductionmentioning
confidence: 99%